Toleransi Antar Umat Beragama dalam Film â€œ?â€ (Tanda Tanya) dan Ayat-Ayat Cinta 2 - Ahmad Zaini (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2020)
This paper aims to find out the discourse of tolerance among religious people featured in the film â€œ?â€ (Tanda Tanya) and Ayat-Ayat Cinta 2. Both are viewed from the level of the text, the level of social cognition, and the level of social context. The research method used is qualitative analysis with Teun van Dijk's theoretical approach, namely data analysis at the level of text, social cognition and social context. The results showed that; First, the discourse of tolerance at the text level in the film â€œ?â€ (Tanda Tanya) is related to various themes, both about harmony among religious communities, cultural diversity and about tolerance. Likewise the film Ayat-Ayat Cinta 2 also tells the story of religious life in European countries. Second, the discourse of tolerance between religious communities is seen from the level of social cognition. In the film â€œ?â€ (Tanda Tanya), both the screenwriter and director want to explain the reality of the diversity of religions, cultures and customs that exist in Indonesia. He wants to explain the relationship between religious people in a vulgar way. In contrast to the more refined Ayat-Ayat Cinta 2 movie. Third, the discourse of tolerance between religious communities in terms of the level of social context. The film â€œ?â€ (Tanda Tanya) is motivated by the number of bombings that occurred at the house of worship three or four years before. At the level of the social context of this film as a sequel to the previous Ayat-Ayat Cinta movie. The background of making this film is because it wants to illustrate that Islam can be used as a way of life wherever we live, including life in the West though. Tulisan ini bertujuan untuk mengetahui wacana toleransi antar umat beragama yang ditampilkan dalam film â€œ?â€ (Tanda Tanya) dan Ayat-Ayat Cinta 2. Keduanya ditinjau dari level teks, level kognisi sosial, dan level konteks sosial. Metode riset yang digunakan adalah analisis kualitatif dengan pendekatan teori Teun van Dijk, yaitu analisis data pada level teks, kognisi sosial dan konteks sosial. Hasil penelitian menunjukkan bahwa; pertama, wacana toleransi pada level teks dalam film â€œ?â€ (Tanda Tanya) berkaitan dengan tema yang beragam, baik itu tentang kerukunan antar umat beragama, keragaman budaya maupun tentang toleransi. Demikian halnya film Ayat-Ayat Cinta 2 juga mengkisahkan tentang kehidupan umat beragama di negara Eropa. Kedua, wacana toleransi antar umat beragama ditinjau dari level kognisi sosial. Dalam film â€œ?â€ (Tanda Tanya) sang penulis skenario maupun sutradara ingin memaparkan realitas tentang keragaman agama, budaya, adat istiadat yang ada di Indonesia. Ia ingin memaparkan hubungan antar umat beragama secara vulgar. Berbeda dengan film Ayat-Ayat Cinta 2 yang lebih halus. Ketiga, wacana toleransi antar umat beragama ditinjau dari level konteks sosial. Film â€œ?â€ (Tanda Tanya) dilatarbelakangi banyaknya kejadian bom yang melanda rumah ibadah pada tiga atau empat tahun sebelumnya. Pada level konteks sosial film ini sebagai sekuel film Ayat-Ayat Cinta sebelumnya. Latar belakang pembuatan film ini karena ingin menggambarkan bahwa Islam dapat dijadikan pedoman hidup dimanapun kita tinggal, termasuk hidup di negeri Barat sekalipun.